SID Property Management / Wan Muhammad Farkhan Wan Aman - Wan Aman, Wan Muhammad Farkhan (Faculty of Business and Management, 2023)
"No matter how many mistakes you make or how slow your progress, you are still a way ahead of everyone who isn't trying," Tony Robbins once said. This quote is refers how process is very important to step up our quality. In 24 weeks of industrial training at SID PROPERTY MANAGEMENT, I had an experience that was both exhilarating and important, and this phrase is apt to describe it. On March 1st 2023,1began my industrial training at SID PROPERTY MANAGEMENT, which will last until August 2023. I was assigned to the Department of Finance and Operation for the Melaka's branch. This report offers an overview of the company and my internship. My readiness for a real working life both physically and mentally was greatly influenced by my prior career. The report will begin with an overview of the background of the company as a whole, including its vision and mission, organizational structure and product supply. I’ve also submitted my resume that details my internship experience. Then, where I go into more detail, which my training outcome. My supervisor, Mr Saiful Islam Bin Dimyati, also a director manager, have helped and guided me understand a lot about how to manage finance and operation in the company. In addition, I included an observation on Sid Property Management that outlined the company’s SWOT analysis. This SWOT analysis is including strengths, weaknesses, opportunities and threats. Besides that, there are also suggestions and in-depth analyses of the discussions. Students will have the skills essential to complete for higher-paying employment after their complete the internship. Additionally, it introduces students to the workforce, where they can develop their talents and becomes more marketable. Besides that, the advantages of industry training include exposing student to the reality of work and helping them develop their personalities, communication skills and discipline by modelling good work ethics and regulations.